ANALISIS FAKTOR – FAKTOR TINGGINYA HARGA LPG 3 KG DI KABUPATEN BARITO UTARA - Tajeri; Rima Puspita; Rus Mala Sari (JURNAL ILMU EKONOMI (MANAJEMEN PERUSAHAAN) DAN BISNIS, 2025)
Abstract This study aims to analyze the factors contributing to the high price of 3-kilogram Liquefied Petroleum Gas (LPG) in Barito Utara Regency. The research focuses on five main aspects: distribution, demand, price regulation, consumer behavior, and suspected stockpiling and diversion by certain individuals. The method used is a descriptive qualitative approach with data collection techniques including observation, interviews, and document study. The results show that the distribution of 3-kg LPG in Barito Utara Regency remains uneven, leading to an imbalance between supply and demand at the end-user level. High demand from non-target consumers has worsened market conditions, exerting pressure on the supply chain and causing prices to rise above the government-determined Retail Price Ceiling (HET). Weak enforcement of pricing regulations has created space for unofficial distribution practices and violations of subsidy policies. On the other hand, consumer behavior that deviates from the intended purpose of the subsidy—such as excessive purchasing and normalization of high prices—has strengthened unregulated informal distribution channels. In addition, there are strong suspicions of stockpiling and diversion of 3-kg LPG by agents and distribution points to gain economic advantage, supported by a significant discrepancy between the realized distribution volume and the estimated actual needs of the intended target groups.